Analysis of combustion characteristics of wood stack and absolute ethanol in fire extinguishing experiment - Chunxiao Liu; Guoqing Zhu; Bingrui Yan; Guanyu Hou; Chun An (Case Studies in Thermal Engineering, 2023)
For the purpose of researching the rules of combustion heat release, ammonium phosphate dry powder extinguishing agent and water-based fire extinguishing agent were utilized before and after the class A fire common wood stack ignition fuel and class B fire anhydrous ethanol ignition fuel fire extinguishing. For wood stack fire, 0.5A wood stack was used for blank combustion test, and the pan fire ignition method for the same type and scale of wood stack fire extinguishing experiment. For absolute ethanol fire, fire suppression was studied using a 13B scale. The change characteristics of the combustion field before and after action of the dry powder extinguishing agent and water system extinguishing agent were measured by thermocouple, heat flow meter and digital camera. The findings of the experiment demonstrated that in the combustion experiment of wood stack, the temperature of 0.5A wood stack of the blank group could reach 800 °C, and the temperature reduction rate of free combustion was 2.62 °C/s. It took an average of 36.5s and 2.25 kg of ammonium phosphate dry powder to put out the fire，and the temperature reduction rate was 4.18 °C/s. The average amount of water-based extinguishing agent used to extinguish a fire was 1.21 kg, yet the average time to do so was just 12.5 s, and the average rate of temperature drop was 10.14 °C/s. In the experiment where an ethanol pool fire was being burned, the typical amount of water-based fire extinguishing chemical used was 3.44 kg, and the typical extinguishing time was 18 s, the maximum temperature drop rate could reach 35.6 °C/s in the initial stage of fire extinguishing, despite the fact that the dry powder fire extinguisher containing ammonium phosphate was used, the fire was not properly controlled.